Associations between infant feeding practices and length, weight, and disease in developing countries - Yarnoff, Benjamin; Allaire, Benjamin; Detzel, Patrick (Frontiers in Pediatrics, 2013)
The health benefits of exclusive breastfeeding are well known, but the relative detrimental impacts of other foods on infant health are unknown. Because infants in developing countries are fed a wide range of food, quantifying the burden of these diverse feeding practices on infant health is essential for public health policy. We used data from the Demographic Health Survey from 20 developing countries over multiple years to examine the independent association of six different types of food (exclusive breastfeeding, nonexclusive breastfeeding, infant formula, milk liquids, non-milk liquids, and solid foods) with five measures of infant health (length, weight, diarrhea, fever, and cough). We estimated associations with regression analysis, controlling for confounding factors with infant, mother, and household factors and community-year fixed effects. We used these estimates in a simulation model to quantify the burden of different combinations of food on infant health. We show that for an infant younger than 6 months old, following current guidelines and exclusively breastfeeding instead of giving the infant solid foods may increase length by 0.75 centimeters and weight by 0.25 kilograms and decrease diarrhea, fever, and cough prevalence by 8%, 12%, and 11%, respectively. We found that the burden on infant health of some feeding practices is less than others. Although all other feeding practices are associated with worse health outcomes than exclusive breastfeeding, breastfeeding supplemented with liquids has a lower burden on infant health than solid foods and infant formula has a lower burden than milk or nonmilk liquids as measured by four of five health metrics. Providing specific quantified burden estimates of these practices can help inform public health policy related to infant feeding practices.